Corpus Callosotomy in 3 Cavalier King Charles Spaniel Dogs with Drug-Resistant Epilepsy - Rikako Asada (MDPI AG, 2021)
Corpus callosotomy (CC) is an established palliative surgery for human patients with drug-resistant epilepsy (DRE), especially those with generalized seizures and multiple or unknown epileptogenic focus. However, there are no reports to describe CC in canine patients with epilepsy. Three client-owned Cavalier King Charles Spaniels with DRE are included in this case series. In presurgical evaluations, an apparent epileptogenic zone was not detected in each dog and CC was conducted. Total CC was performed in one dog, whereas the other two received partial CC. One dog recovered from surgery without any complications, but died suddenly by an unknown cause at 10 h after surgery. For the other two dogs, postoperative evaluations including seizure outcomes, complications, and quality of life of the dogs and owners were assessed for at least 12 months. Both dogs showed a remarkable decrease in seizure frequency (averaged 80.3% reduction) and severity after surgery. The antiseizure medications were maintained, and not only the mentation and activity of the dogs, but also the quality of life of dogs and owners were improved postoperatively. Although technical improvement and more large-scale studies are needed, CC is a treatment option for dogs with DRE in veterinary medicine.